Women Fighting Peatland Fire: Rural Women’s Experiences in Central Kalimantan and Riau Provinces - Indirastuti, Catharina (Yayasan Jurnal Perempuan, 2020)
Forest and land fire that repeatedly destroyed million hectares of peatland in Indonesia is a result of unsustainable peatland governance for many years. Rural women and men living in peatland have different experiences with forest and land fire. Intersectionality between gender and class, geographical location, and ethnicity further add nuances to these different experiences. This article explores women experiences in fighting peat forest and land fire in 3 target villages of Peat Care Village Program led by Peat Restoration Agency in Central Kalimantan and Riau. Power network that women must endure and a priori on gendered roles and responsibilities weaken women’s position in fighting peatland fire. Women do not have access to resources given to prevent and fight against forest and land fire, while in reality fire fighting activities require women’s involvement especially when it happened in their land or living space. Women experiences in facing peat forest and land fire is reflected using feminist political ecology approach to highlight the multiple impacts that women experience.